Identification of prolyl hydroxylation modifications in mammalian cell proteins. Issue 7 (19th January 2015) - Arsenault, Patrick R.; Heaton‐Johnson, Katherine J.; Li, Lin‐sheng; Song, Daisheng; Ferreira, Vinicius S.; Patel, Nish; Master, Stephen R.; Lee, Frank S.
<x xml:space="preserve">Abstract</x> Prolyl hydroxylation is a PTM that plays an important role in the formation of collagen fibrils and in the oxygen‐dependent regulation of hypoxia inducible factor‐α (HIF‐α). While this modification has been well characterized in the context of these proteins, it remains unclear to what extent it occurs in the remaining mammalian proteome. We explored this question using MS to analyze cellular extracts subjected to various fractionation strategies. In one strategy, we employed the von Hippel Lindau tumor suppressor protein, which recognizes prolyl hydroxylated HIF‐α, as a scaffold for generating hydroxyproline capture reagents. We report novel sites of prolyl hydroxylation within five proteins: FK506‐binding protein 10, myosin heavy chain 10, hexokinase 2, pyruvate kinase, and C‐1 Tetrahydrofolate synthase. Furthermore, we show that identification of prolyl hydroxylation presents a significant technical challenge owing to widespread isobaric methionine oxidation, and that manual inspection of spectra of modified peptides in this context is critical for validation.